Revision of the genus Pteroplatus Buquet, 1840 (Coleoptera, Cerambycidae, Cerambycinae) and taxonomic notes in Pteroplatini - Botero, Juan Pablo; Santos-Silva, Antonio; Bezark, Larry G. (Zootaxa, 2019)
A revision of the genus Pteroplatus Buquet, 1840 is presented. The genus and all known species are redescribed. Pteroplatus luculentus sp. nov., from Colombia and Ecuador, is described. The following six syn. nov. are proposed for Pteroplatus pulcher Buquet, 1840: Pteroplatus atroviolaceus Kirsch, 1889; Pteroplatus dimidiatipennis Buquet, 1841; Pteroplatus elegans Buquet, 1841; Pteroplatus fasciatus Buquet, 1841; Pteroplatus nigriventris Brême, 1845, and Pteroplatus transversalis Brême, 1845. The following two syn. nov. are proposed for Pteroplatus gracilis Buquet, 1840: Pteroplatus caudatus Martins & Galileo, 2013 and Pteroplatus rostainei Buquet, 1840. The following two comb. nov. are proposed: Corynellus arrogans (Buquet, 1840) (Pteroplatini) and Cosmoplatidius bilineatus (Buquet, 1841) (Compsocerini). In addition, the following syn. nov. is proposed: Pteroplatus sellatus White, 1853 = Cosmoplatidius bilineatus (Buquet, 1841). The geographical distribution of four species is expanded. Photographs of Pteroplatus species are included and a key to differentiate the species is provided.